ANALISIS PENGARUH HARGA DAN KUALITAS PELAYANA TERHADAP KEPUASAN PELANGGAN XOVID 20 - Yoga, I Wayan Suprapta; Prawitasari, Putu; Suidarma, I Made; Adyatna Wedananta, Kadek (Jurnal Bina Bangsa Ekonomika, 2025)
The research aims to answer the question, "How does price and quality of service affect customer satisfaction?" in two ways: separately and together. The study surveyed 108 XOVID 20 users. The data were analyzed using a variety of approaches, including validity and reliability tests, multiple linear regression analysis, determination coefficient tests, F-tests, t-tests, and classical assumption tests. According to the results of the study, price has a positive and substantial effect on customer satisfaction, service quality has a positive and significant effect on consumer satisfaction, and both price and service quality have a major impact on consumer satisfaction. Sixty-six percent is the level of influence of independent variables on consumer happiness. Researchers can recommend that XOVID 20 periodically run promotions by offering discounts, educating employees to solve customer problems, and improving the quality of services offered to clients.